The Development of Writing Materials Based on Learning Strategy in Enhancing Student Writing Achievement at SD IT Bunayya Tangerang in 2021/2022 Academic Year - Amdani, Zuly; Hasibuan, Ahmad Laut (International Journal of Educational Research Excellence (IJERE), 2024)
The purpose of this study is to find out the relationship between reading habits and the ability to write in English.The tests were pre-test and post-test. To analyze the qualitative data, the researcher used interactive data analysis models. For the quantitative data, the researcher analyzed the mean scores of the tests to compare differences between pre-test and post-test. The results of the research show that teaching writing skills by using pictures could improve the students' writing skills and the class condition.The method used in this study is a descriptive method with correlation analysis techniques. The population of this study was all V grade students of SDIT Bunayya Tangerang academic year 2021-2022, totaling 23 students who were used as samples. The instruments used in data collection are questionnaires, objective tests and essay tests. Questionnaires are used to get data about students' reading habits, objective tests are used to get data about creative thinking skills and essay tests are used to get data about the ability to write in English subject of students.